Bivalve taxonomic diversity throughout the Italian Pliocene as a tool for climatic-oceanographic and stratigraphic inferences - Raffi, S. (1992)
The state of research on the evolution of marine bivalve taxonomic diversity of the Mediterranean Pliocene is analysed. The following assertions are discussed: 1) The Early Pliocene malacofauna is characterized by a high number of warm-water taxa and a high taxonomic diversity with respect to that of the present time. 2) The first appreciable extinction event in the Mediterranean Pliocene approximates or just follows the FO of Globorotalia bononiensis. 3) The second appreciable extinction event is between the LAD of Discoaster tamalis and the LAD of Discoaster surculus . 4) A third minor extinction event is penecontemporaneous with the FO of Globorotalia inflaia. Taking into account the available data on the Pliocene extinction events it has been possible to distinguish 4 different molluscan units with different climatic-oceanographic significance.